Project-based R companion to introductory statistics - Myers, Chelsea (Boca Raton : Chapman & Hall/CRC, 2020)
"One of the most difficult transitions students face when beginning a first "real" job after college is moving beyond solving the well-designed problems found in textbooks to tackling the messy, complex problems they face in the real world. Statistics: A Project-Based Approach Using R is designed as a companion text for undergraduate students who wish to learn basic R programming and gain experience analyzing data from larger, real-world projects. Topics covered include working with R and RStudio, basic descriptive statistics, two-way tables, simple linear regression and hypothesis testing for means and proportions"--
OCLC-licensed vendor bibliographic record.
Keywords: Mathematical statistics -- Data processing; R (Computer program language); MATHEMATICS / Probability & Statistics / General